Hubungan Power Otot Tungkai dengan Jarak Tendangan Jauh dalam Sepakbola SSB Arofa - Rizky Fauzan Irawan; Encep Sudirjo; Dinar Dinangsit (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the relationship between leg muscle power and long kick distance in soccer players of SSB Aroffa. A quantitative correlational design was employed with 30 athletes as the sample. The instruments used were the vertical jump test and long kick test. Data were analyzed using Pearson correlation. The results showed a correlation coefficient of 0.188 with a significance value of 0.320 (>0.05), indicating no significant relationship between the variables. It can be concluded that long kick distance is not only influenced by leg muscle power but also by other factors such as technique and coordination. Keywords: Leg Muscle Power, Soccer, Long Kick